Analysis of Leading Horticultural Fruit Commodities in the Agropolitan Area of Bojonegoro Regency - Andriniswari, Fiebri; Agustin, Imma Widyawati; Waloejo, Budi Sugiarto (Fakultas Teknik Universitas Brawijaya, 2024)
The development of agricultural program plans with superior products in certain agribusiness regions in order to boost revenue and significantly empower the area. This is being done in an effort to enhance the government-backed agrobusiness system and agropolitan area development. Regarding RTRW, Bojonegoro Regional Regulation Number 5 2021 designates Dander Kapas Kalitidu Trucuk as the agropolitan area. Bojonegoro's 2022 An examination of superior commodities in the Bojonegoro agropolitan area is necessary in order to create a development plan for the agriculture industry. The study's findings can be utilized to drive the agropolitan region of Bojonegoro Regency's development in a way that will enhance community welfare and spur local economic expansion. Shifts Share Analyzes (SSA) and Location Quotient (LQ) analyses were employed in this study. This study's findings indicate that the star fruit commodity, with a LQ value of 1.13 and an SS value of 33.87, the guava commodity, with a LQ value of 1.91 and an SS value of 6819.19, the Siam orange commodity, with a LQ value of 2.33 and an SS value of 8.25, and the snake fruit commodity, with a LQ value of 3.16 and an SS value of 21.75, are the superior commodities. The Bojonegoro agropolitan area is witnessing the development of exceptional fruit horticulture, indicating that a holding and maintaining plan would be the most effective approach for managing the organization. Strategies for product creation and market penetration are used. The strategy calls for increasing the product's quality, expanding its distribution networks, marketing it, and changing market prices.